Pembinaan Kewirausahaan Pada UMKM Bahagia di Nagari Kubang Kecamatan Guguak Kabupaten Limapuluh Kota - Elva Rahmi Fitri; Situmorang, Helentina; Latifa, Dara; Azel, Farid; Putrina, Misfit (Journal of Community Engagement Research for Sustainability, 2022)
UMKM are one of the most powerful activators of the economies and make a significant contribution to spurring the economy in Indonesia. The purpose of this community service activity is to increase knowledge and skills regarding business financial management and be able to make their own books so that they are orderly in carrying out financial records. The method used is by way of training. This Simple Bookkeeping training activity is very helpful for women in recording every financial transaction related to their business. In conclusion, every member of this activity is able and willing to apply this bookkeeping to their business for the smooth and development of their business. As well as being able to make their own books so that they are orderly in carrying out their financial records.